Anglo-German relations during the Labour governments 1964-70 : NATO strategy, détente and European integration - Macintyre, Terry (Book collections on Project MUSE., 2007)
Speaking at West Point in 1962, Dean Acheson observed that Britain had lost an empire and had still to find a new role. This book explains why, in the following years, as Britain?s Labour government contemplated withdrawal from east of Suez, ministers came to see that Britain?s future role would be as a force within Europe. To this end, and in order to gain entry into the European Economic Community, a close relationship with the Federal Republic of Germany would be essential. This account of Anglo-German relations during the 1960s reveals fascinating insights into how both governments reacted.